Analisis Peran Auditor Eksternal dan Karakteristik Perusahaan Terhadap Lamanya Penyelesaian Audit Laporan Keuangan di PT Asabri (Persero) Palembang - Emilia Gustini; Kharisma Kartini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of the role of external auditors and company characteristics on the timeliness of financial statement audit completion (audit delay) at PT Asabri (Persero) Palembang. Audit delay is an important indicator in assessing the timeliness of financial reporting, which affects the relevance of information for stakeholders. This research uses a quantitative approach with data collection techniques through documentation and literature study, and is analyzed using multiple linear regression to examine both partial and simultaneous effects. The results show that the role of external auditors and company characteristics have a significant effect on audit delay, both partially and simultaneously. Therefore, improving the quality of external auditors and managing company characteristics effectively are expected to accelerate the completion of financial statement audits.